Dynamic R&D networks - Michael D. König (University of Zurich, Department of Economics, 2013)
In this paper we analyze R&D collaboration networks in industries where firms are competitors in the product market. Firms' benefits from collaborations arise by sharing knowledge about a cost-reducing technology. By forming collaborations, however, firms also change their own competitive position in the market as well as the overall market structure. We analyze incentives of firms to form R&D collaborations with other firms and the implications of these alliance decisions for the overall network structure. We provide a general characterization of both equilibrium networks and endogenous production choices, and compare it to the efficient network architecture. We also allow for firms to differ in their technological characteristics, investigate how this affects their propensity to collaborate and study the resulting network architecture.
Keywords: C63; D83; D85; L22; 330; Bonacich centrality; network formation; R&D networks; Industrielle Forschung; Forschungskooperation; Technischer Fortschritt; Unternehmensnetzwerk; Theorie